2016
DOI: 10.1111/jpy.12467
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of jasmonates during cystocarp development in the red alga Grateloupia imbricata

Abstract: In this study, we highlight the effects of methyl jasmonate (MeJa) on cystocarp development in the red macroscopic alga Grateloupia imbricata. In G. imbricata, jasmonate release is related to the reproductive state, as fertile thalli (i.e., those that have cystocarps) released significant amounts of this volatile compound (1.27 ± 0.20 mM · mg fw · h ) compared with infertile thalli (0.95 ± 0.12 mM · mg fw · h ). Treating G. imbricata thalli with MeJa revealed a significant increase in cystocarp number (1.5 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Studies of in vitro carposporogenesis in G. imbricata have demonstrated that polyamines, ethylene, and methyl jasmonate act as elicitors of cystocarp development, spore release, and the timing of the development of reproductive structures; moreover, knowledge of the functional mechanisms of these elicitors has informed the search for candidate genes that govern reproduction in red algae [5,8,9,12]. Therefore, in our transcriptome analysis, we selected transcripts related to polyamine metabolism such as ornithine decarboxylase (ODC), SAMS, SAM decarboxylase, copper amine oxidase, spermidine/spermine synthase, putrescine aminopropyltransferase, agmatine deimidase, and N-carbamoylputrescine amidohydrolase (supplementary file 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of in vitro carposporogenesis in G. imbricata have demonstrated that polyamines, ethylene, and methyl jasmonate act as elicitors of cystocarp development, spore release, and the timing of the development of reproductive structures; moreover, knowledge of the functional mechanisms of these elicitors has informed the search for candidate genes that govern reproduction in red algae [5,8,9,12]. Therefore, in our transcriptome analysis, we selected transcripts related to polyamine metabolism such as ornithine decarboxylase (ODC), SAMS, SAM decarboxylase, copper amine oxidase, spermidine/spermine synthase, putrescine aminopropyltransferase, agmatine deimidase, and N-carbamoylputrescine amidohydrolase (supplementary file 2).…”
Section: Resultsmentioning
confidence: 99%
“…Methyl jasmonate induces both cystocarp maturation and sporulation [5]. In higher plants, jasmonic acid is synthesized by the oxygenation of linolenic acid via lipoxygenase, and a methyl group is then added to jasmonic acid, which yields methyl jasmonate; however, in seaweeds which perceive and respond to methyl jasmonate, the relevant biosynthetic enzymes have not been characterized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes related to the maturing of thalli are favoured by volatile growth regulators, which also lead to both cystocarps dehiscence with a marked reduction of the maturity period, and the presence of different reproductive structures in the same individual [5]. Moreover, other evidence such as sudden losses of seaweed mats and alternating life cycles could also give cues on how volatile compounds act as a signal to trigger the reproductive process.…”
Section: Introductionmentioning
confidence: 99%